2009
DOI: 10.4314/njo.v16i2.46740
|View full text |Cite
|
Sign up to set email alerts
|

Chalazion, a Benign Eyelid Tumour – The Sagamu Experience

Abstract: Aim: To study the demographic characteristics, pattern of presentation and type of treatment of chalazion in Sagamu, Nigeria. Materials and Methods: A retrospective hospital-based study was conducted to review all the cases seen and diagnosed as chalazion in the eye clinic of Olabisi Onabanjo University Teaching Hospital [OOUTH], Sagamu between January 1997 and December 2007. Data was obtained from the clinic attendance register, the register of minor office procedure and the case files. The age, sex, pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…13 The incidence in Nigeria was reported to be 0.7% in one study. 14 Some studies report a sex difference in the incidence of chalazion with females experiencing higher rates of lesions. 1,8 This is often attributed to the hormonal influence of sebum production especially during puberty and pregnancy.…”
Section: Incidence Of Chalazionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The incidence in Nigeria was reported to be 0.7% in one study. 14 Some studies report a sex difference in the incidence of chalazion with females experiencing higher rates of lesions. 1,8 This is often attributed to the hormonal influence of sebum production especially during puberty and pregnancy.…”
Section: Incidence Of Chalazionmentioning
confidence: 99%
“…Chalazion occur in all ages, but it occurs maximally in children and adults below the age of 30 years probably due to the higher level of androgenic hormones that stimulate sebum production and viscosity. 3,14 The mean age of chalazion was reported to be around 25 years, and more than two thirds of the cases were found to occur during the second and third decades of life. 16 Chalazia are more common in the upper lids due to the higher number of tarsal glands in comparison to the lower lids.…”
Section: Incidence Of Chalazionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study female 65(58%) were affected more than male 47(42%), as found in previous studies. 6,7 Chalazion occurs across all ages, it may cluster at puberty but it is less prevalent among the elderly 6 . Similar to other studies maximum incidence was seen in age group 17-30(67.9%) because of higher level of androgenic hormones which increases seabumviscosity.…”
Section: Discussionmentioning
confidence: 99%